TINDAKAN EXTRAJUDICIAL KILLING TERHADAP TERDUGA PELAKU TINDAK PIDANA TERORISME DALAM PERSPEKTIF ASAS PRESUMPTION OF INNONCENT DAN HAM - I Ketut Astawa; Daud Munasto (Magister Hukum Sekolah Pascasarjana Unida, 2022)
There have been a number of terrorist incidents in Indonesia that have led to extrajudicial killings in several cases by the police. Extrajudicial killing is an act that is carried out on the basis of the discretion of certain authorities to carry out acts of murder against perpetrators suspected of committing crimes of terrorism. Criminal acts of terrorism are regulated in Law Number 2 of 2002 concerning Eradication of Criminal Acts of Terrorism, the meaning of terrorism is a deliberate attack on public order so as to cause fear to the wider community. In criminal procedural law there is the principle of presumption of innocence, which means that a person is considered innocent before a judge's decision has permanent legal force. Because everyone also has human rights that must be protected by anyone, especially the police as law enforcers. This writing uses a normative juridical method, namely the study of legal principles, legal systematics, and legal comparisons. In addition, it discusses the doctrines in the science of law, and this writing has a descriptive-analytical philosophy that describes in detail, systematically, and thoroughly.